Darkness and day - Compton-Burnett, I. (Ivy), 1884-1969. (London : Gollancz, 1967)
Small Osa is fearless during the day, climbing trees or exploring the African valley where she lives, but at night she becomes afraid of the strange and terrifying things that might lie in the dark.